2017
DOI: 10.1002/celc.201701094
|View full text |Cite
|
Sign up to set email alerts
|

From Water and Ni Foam to a Ni(OH)2@Ni Foam Binder‐Free Supercapacitor Electrode: A Green Corrosion Route

Abstract: In this work, a Ni(OH)2@Ni foam binder‐free electrode was obtained through the corrosion of Ni foam with ultrapure water under hydrothermal conditions. The structure, morphology, and surface chemical states of the obtained Ni(OH)2@Ni foam were characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and X‐ray photoelectron spectroscopy. The chemical formation mechanism is discussed. In addition, it was found that the loading amount and morphology of the deposited Ni(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
(63 reference statements)
2
6
0
Order By: Relevance
“…Galvanostatic charge and discharge curves at 1 A•g −1 are shown in Figure 3. In KOH electrolyte, there is a charging/discharging platform, while there are two obvious charging/discharging platforms at about 0.4 and 0.5 V in K 3 [Fe(CN) 6 ] + KOH electrolytes, which further confirms existence of multi-step redox process in K 3 [Fe(CN) 6 ] + KOH system [10].…”
Section: Galvanostatic Charge and Discharge Testsupporting
confidence: 52%
See 1 more Smart Citation
“…Galvanostatic charge and discharge curves at 1 A•g −1 are shown in Figure 3. In KOH electrolyte, there is a charging/discharging platform, while there are two obvious charging/discharging platforms at about 0.4 and 0.5 V in K 3 [Fe(CN) 6 ] + KOH electrolytes, which further confirms existence of multi-step redox process in K 3 [Fe(CN) 6 ] + KOH system [10].…”
Section: Galvanostatic Charge and Discharge Testsupporting
confidence: 52%
“…In KOH electrolyte, a pair of main redox peaks appeared in CV curve at about 0.34 V and 0.56 V (vs HgO/Hg) at scanning rate of 0.01 V•s −1 , which could be attributed to the transition between Zn(II) and Zn(III) of HZC electrode. The HZC electrode showed typical pseudocapacitance characteristics [10] [11]. In , and the deviation of redox peak may be related to properties of substrate, surface roughness of substrate, or superpotential of electrode [12].…”
Section: Cyclic Voltammetry Analysismentioning
confidence: 96%
“…24 Liu et al prepared Ni(OH) 2 in Ni-foam by corrosion and showed 863 mF cm À2 , stability up to 77.3% for 3000 cycles. 25 Similar Ni 3 S 2 synthesis studies have been reported using Ni-foam as a conductive matrix 19,[26][27][28][29] or a sacrificial template of Ni(OH) 2 on Nifoam. [30][31][32] These studies included precursor composition and hydrothermal conditions' effect on material growth.…”
Section: Introductionsupporting
confidence: 53%
“…Using this analogy, Chen et al prepared Ni 3 S 2 nanoparticles on a Ni‐foam electrode delivered 1120 mF cm −2 with no degradation up to 3000 cycles 24 . Liu et al prepared Ni(OH) 2 in Ni‐foam by corrosion and showed 863 mF cm −2 , stability up to 77.3% for 3000 cycles 25 . Similar Ni 3 S 2 synthesis studies have been reported using Ni‐foam as a conductive matrix 19,26‐29 or a sacrificial template of Ni(OH) 2 on Ni‐foam 30‐32 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to further improve the rate performance and cycling stability of electrode materials for supercapacitors, one promising strategy is to build three dimensional core‐shell heterostructures combining the advantages of individual materials directly on various substrates, such as cellulose fiber, graphene foam, carbon nanofiber, Ti foil and Ni foam . To date, researchers have successfully constructed a wide variety of well‐defined core‐shell nanostructures with superior supercapacitive performance.…”
Section: Introductionmentioning
confidence: 99%